Soil coarsening alleviates precipitation constraint on vegetation growth in global drylands - Xinrong Zhu; Hongyan Liu; Chongyang Xu; Lu Wu; Liang Shi; Feng Liu (Environmental Research Letters, 2022)
Drought is an important and complicated topic, and the specific variables that are considered to represent climate drought stress and plant water stress often generate highly contradictory conclusions. As the junction of the atmosphere and the biosphere, soil may play an important role in separating climatic drought stress from vegetation water constraint. Here, we conduct a comprehensive evaluation of water constraint on vegetation growth in global drylands by separating precipitation constraint and soil moisture constraint. Although global drylands are characterized by low precipitation supply capacity, there are indeed a large number of grids showing decoupled water availability for plants from variability of precipitation, with ratios of 47%, 64%, and 61% for arid, semiarid, and subhumid regions, respectively. Soil properties, instead of climate and root length regimes, can explain the water constraint divergence between precipitation and soil moisture. Sand content emerges as the most significant soil property to weaken the precipitation constraint on vegetation growth, with a 1% increase in sand content of global arid, semiarid, and dry subhumid regions increasing an average of 0.31, 0.45, and 0.04 gC m ^−2 yr ^−1 gross primary productivity (GPP) deviation from the theoretical GPP determined by precipitation, respectively. This study provides new insight into how soil texture interacts with precipitation constraints to influence plant-available water in global drylands, which contributes to assessing ecological drought in global drylands.